The Managerial Capabilities of Guidance and Counseling Teachers in Implementing Guidance and Counseling Programs in Schools - Chana Indika; Firman; Neviyarni S (Manajia: Journal of Education and Management, 2024)
This study discusses the managerial skills of guidance and counseling (BK) teachers in the implementation of counseling programs in schools. Managerial skills, effective communication, and in-depth counseling skills are the key aspects analyzed in the context of effective counseling service provision. Collaboration with various parties in the school and the utilization of modern technology are also discussed as improvement factors in the management and accessibility of services. This study utilizes a literature study method or commonly referred to as the literature study method. The results of the study on the managerial skills of guidance and counseling (BK) teachers in the implementation of school counseling programs show that managerial, communication, and counseling skills play an important role in the effectiveness of the BK program. This study reveals that guidance and counseling teachers who have strong managerial skills tend to be able to organize guidance and counseling programs more efficiently, plan activities in accordance with student needs, and manage available resources optimally.